Charge Accumulation Processes in Electrochemical Systems Formed from Laser Irradiated Composite TiO2/C - I.М. Budzulyak; R.V. Ilnytsky; О.V. Morushko; B.I. Rachiy; О.М. Hemiy; L.О. Shyyko; L.S. Yablon (Журнал нано- та електронної фізики)
The electrochemical system based on laser irradiated composite of nanoscale titanium dioxide/nano-porous carbon is formed, the charge accumulation processes in this system depending on the composition of the composite and the impact of the laser irradiation on these processes are studied. It is shown that the laser irradiation increases the specific capacity of the composite systems 50 times at the discharge cur-rent of 5 mA, which is a result of the emergence of new and modified guest positions in composite compo-nents.